Experimental analysis on the effect of cooling surface area and flow rate for water cooled photovoltaic module - Mohamad Firdaus, Basrawi; Anuar, M. N. A. F.; Ibrahim, T. K.; A. A., Razak (IOP Publishing, 2020)
Application of water spray or water flow on the surface of photovoltaic (PV) modules is one of the techniques used to increase efficiency. Main parameter that affect the performance by this technique is water flow rate and cooling surface are. However, there is less study focus on those parameters. Thus, the objective of this paper is to investigate the effect of water-cooled surface area and water flow rate on the temperature and power output of the PV. Orifices were used to create half-cooled and fully-cooled surface area for water to flow as cooling techniques while the hand valve was used to control the flow rate of water at 120 L/h, 180 L/h and 240 L/h flowing onto the panel. A solar simulator was constructed and used to provide 600 W/m2, 1,000 W/m2, and 1,200 W/m2 irradiance for the panel. The testing methodology consists of three different experiments for each irradiance level. It was found that more cooling surface area covered could significantly reduce temperature in any irradiance level, and fully-cooled module could keep the temperature at below 40 °C eventhough the irradiance was at 1,200 W/m2. In addition, the optimum flow rate also depends on the cooling surface area. Thus, there is a unique relation between cooling surface area and optimum flow rate. Thus, further investigation is needed on this relation.